Fibrous capsule formation of the peritoneal catheter tip in ventriculoperitoneal shunt: Two case reports - Kano, Tomoaki (Surg Neurol Int, 2014)
BACKGROUND: A fibrous capsule formation of a peritoneal catheter tip has not previously been researched as a complication of ventriculoperitoneal (VP) shunts. CASE DESCRIPTION: Two adult patients who had undergone a VP shunt for communicative hydrocephalus following subarachnoid hemorrhage caused by a ruptured aneurysm have been identified with malfunction of the VP shunt system by mild disturbance of consciousness and gait disturbance or loss of appetite. Hydrocephalus was diagnosed by computed tomography and the obstruction of the peritoneal catheter was revealed by shuntgraphy. Laparoscopy was performed and the peritoneal catheter tips were obstructed by fibrous white capsules that covered them. One was a thin membranous capsule like a stocking with two small endoluminal granulomas of the peritoneal catheter, and other one was a fibrous glossy white capsule like a sock. These fibrous capsules were excised by laparoscopy forceps without the conversion to a new peritoneal catheter. Following the procedure, the shunt functioned normally. The pathological diagnoses were peritoneum with foreign body reaction or hyalinization of membranous tissue surrounded by fibrous tissue. CONCLUSION: These fibrous capsules might be formed by the peritoneal reaction to cerebrospinal fluid as a foreign material. As such, a periodic medical check should be scheduled since a fibrous capsule of the peritoneal catheter tip might be formed again.